PEMANFAATAN PENASIHAT AKADEMIK OLEH MAHASISWA FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI YOGYAKARTA - Suhardi Suhardi (Jurnal Cakrawala Pendidikan, 2009)
AbstractThis study described the consultation opportunity, consultation materials,reasons, academic advisors (AAs) responses, students responses, and effects ofAAs guidance on students achievement. The research subjects comprised studentsof the Faculty of Languages and Arts, the Yogyakarta State University, consistingof two groups, namely those who were interviewed (selected by the snow balltechnique) and those who were given an open questionnaire (selected by thestratified random technique). The data were analyzed using the qualitativedescriptive technique. The data credibility was enhanced by the participationlengthening, interview details, triangulation, and peer checking. The results wereas follows. (1) In general, the students consulted with their AAs during theconsultation period. (2) On the average, the consultation frequency was once ortwice a semester. (3) They consulted with not only their AAs but also otherlecturers. (4) They consulted with their AAs when they needed their AAs and theAAs responded to them; they consulted with other lecturers when they found itdifficult to see their AAs, they felt scared and hesitant, and the AAs did notrespond to them. (5) Most consultation materials were academic in nature. (6) MostAAs gave the students positive responses and only few AAs were not responsiveor indifferent. (7) Most of the AAs suggestions were positive and only few wereuseless and irrelevant. (8) The students suggested that AAs should be easy to see,have schedules, and conduct the consultation not in public. (9) Constraints in theconsultation included the difficulty to see AAs because they were busy, therelationship which was not close, the students who were not open, shy, scared andhesitant to see their AAs, and the large number of students. (10) Most studentsrealized the contribution of the consultation with their AAs to their achievement.Keywords: Academic Advisor, academic consultation